2020
DOI: 10.1007/s11269-020-02581-w
|View full text |Cite|
|
Sign up to set email alerts
|

On the Applicability of the Expected Waiting Time Method in Nonstationary Flood Design

Abstract: Given a changing environment, estimating a flood magnitude corresponding to a desired return period considering nonstationarity is crucial for hydrological engineering designs. Four nonstationary design methods, namely expected waiting time (EWT), expected number of exceedances (ENE), equivalent reliability (ER), and average design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The phenomenon is highly generated by the ENE method because of its calculative restriction relying on covariate length. Hence, the computation will definitely bring about higher levels of uncertainties [22]. However, the abovementioned results indicate that the occurrence periods of AMFP estimated by a climate-informed model are longer than return periods under a stationary model, which will be conservative for decision makers in considering the significant climatic factors in current conditions.…”
Section: Return Period and Associated Uncertainty Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…The phenomenon is highly generated by the ENE method because of its calculative restriction relying on covariate length. Hence, the computation will definitely bring about higher levels of uncertainties [22]. However, the abovementioned results indicate that the occurrence periods of AMFP estimated by a climate-informed model are longer than return periods under a stationary model, which will be conservative for decision makers in considering the significant climatic factors in current conditions.…”
Section: Return Period and Associated Uncertainty Analysismentioning
confidence: 97%
“…The results indicated that ENE, DLL and ER yielded very similar design flood values for both increasing and decreasing trends. Yan et al (2020) focused on applying the EWT method to estimate the design flood quantiles and proposed the extrapolation time to guarantee the convergence of the EWT [22]. Given the advantages and disadvantages of these methods [23,24], we choose the ENE method to calculate design floods under a changing climate and the estimated stationary design floods serve as a benchmark for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Water resources are important for social and economic development and the ecological environment, and accurate runoff forecasting can provide a reasonable decision-making basis for the optimal allocation and utilization of water resources (Huang et al, 2014;Xiong et al, 2019;Feng et al, 2020a;Yan et al, 2021a;Jian et al, 2022). However, under changing environments, the runoff process and associated hydrological system have been altered by human activities and climate change (Song et al, 2018;Sun et al, 2018Sun et al, , 2022Jiang et al, 2019;Lu et al, 2020;Yan et al, 2020;Hu et al, 2022), and the runoff series becomes nonlinear and nonstationary, which makes it challenging to capture the variation characteristics of runoff (Sun et al, 2014;Lin et al, 2020;Yan et al, 2021b;Samantaray et al, 2022a;Samantaray et al, 2022b;Samantaray et al, 2022c;Zhou et al, 2022). Therefore, there is an urgent need to develop a runoff prediction model with robustness and high forecasting accuracy under a changing environment (Sit et al, 2020;Niu et al, 2021;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Under the framework of NFFA, if we still follow the design method under stationarity, we can obtain annual design flood for a given return period, which is impractical for engineering design since the relationship between design flood and return period is no longer one-to-one. To address the problem of design flood estimation in NFFA, researchers have carried out many studies and developed several design flood methods in recent years (Olsen et al 1998;Parey et al 2007Parey et al , 2010Cooley 2013;Rootzén & Katz 2013;Acero et al 2017Acero et al , 2018Hu et al 2018;Wang et al 2019;Byun & Hamlet 2020;Lu et al 2020;Yan et al 2020). Yan et al (2019a) comprehensively compared different methods and recommended the use of average design life level (ADLL) and equivalent reliability (Hu et al 2018).…”
Section: Introductionmentioning
confidence: 99%